TRANSFORMASI VISUAL: ANALISIS FORMALISME DALAM COMPOSITION V DAN COMPOSITION VII KARYA WASSILY KANDINSKY - A F, Muhamad Fathur Rouf (Universitas Mercu Buana, 2023)
This study analyzes visual transformation through the formalist approach in two iconic works by Wassily Kandinsky,